The gunpowder plot terror & faith in 1605 - Fraser, Antonia 1932- (Phoenix, 2002)
Antonia Fraser, a popular historian, has delved into archives across Europe to unravel the true story of the plot by fanatical Roman Catholics to blow up the Houses of Parliament and King James I at the opening of Parliament in 1605.